KONSEP HEDONISME EPIKUROS DAN SITUASI INDONESIA MASA KINI - Sudarsih, Sri (HUMANIKA, 2011)
Epikuros regards pleasure as the highest life purpose of human being and then he defines the real pleasure in a concept named ataraxia, i.e. tranquility or quietness. To experience pleasure, one needs to learn how to use each desire to attain health and the tranquility of soul. Hence human being should be wise in responding or handling his desires in order he may arrive at his true purpose of life. Fraternity and friendship are urgent instruments to achieve pleasure. Epikuros also maintain that pleasure should be understood as the balance between physical and spiritual, between individual and social, man-as-an-independent-self and man-as-the-creature-of-God aspects of man. Â  Keywords: hedonism, comfort, wisdom, ataraxia, tranquility.